Digital Engagement and Technology Acceptance among the Muslim Community in Denmark: A TAM Approach - Yusriani, Sri; Patiro, Shine Pintor Siolemba (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This study investigates the Technology Acceptance Model (TAM) within the Muslim community in Denmark, focusing on digital engagement and its impact on religious and community activities. The study aims to understand how perceived usefulness, perceived ease of use, self-efficacy, attitude, and behavioural intention influence the acceptance of digital platforms among Muslim users. Using a structured questionnaire and analysing responses with Structural Equation Modelling (SEM) using AMOS, the study identifies significant predictors of technology acceptance and their interrelationships in the context of digital Islam. The results demonstrate that all hypotheses are supported, indicating a strong influence of perceived ease of use and self-efficacy on both attitude towards technology and its perceived usefulness. This study contributes to the broader discourse on digital Islam, offering insights into how digital tools can enhance religious and social interactions within Muslim communities. The findings provide practical implications for designing culturally sensitive digital solutions tailored to the needs of the Muslim community in Denmark, with a unique unit analysis that provides readers with new knowledge in this field.